Transformasi Limbah Sawit Menjadi Kompos Organik: Upaya Edukasi dan Peningkatan Kemandirian Petani: Penelitian - Nova Yanti; Zulfia Siska Wati (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
Palm oil waste management is a major challenge in palm oil-producing areas, including Pematang Obo Village. Poorly managed palm oil waste can cause environmental pollution, such as soil and water contamination, and produce unpleasant odors that disturb the community. To address these issues, the Pematang Obo Village community has developed a palm oil waste composting process, offering an environmentally friendly and beneficial alternative to waste management. The composting process involves collecting waste such as fibers, fronds, and fruit skins, then crushing them to facilitate their decomposition. The waste is mixed with additional organic materials such as rice bran and livestock manure, then undergoing a fermentation process for 2 to 3 months. The final product is nutrient-rich compost that can be used to improve soil fertility. The use of this compost not only reduces the negative impact of palm oil waste on the environment but also helps increase agricultural productivity for the Pematang Obo Village community. In addition to its ecological benefits, compost cultivation also provides social and economic benefits, such as reducing the cost of purchasing chemical fertilizers and opening up new business opportunities for villagers. Utilizing palm oil waste into compost in Pematang Obo Village is a cheap,